On the Development of Web-GUI Interface for Analyzing Polytomous Responses - Tika Clarinta Putri Utama; Indriasih Yanuwijaya; I Made Tirta (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
One type of measurement often done in education are measurement of the students’ performance both for cognitive and affective aspects. These measures are extremely important therefore must use a good measuring tool and the results also easy to interpret. The measurement of students performance mostly use tests. Measurement test have evolved from traditional one to modern theories to apply more realistic models which are known as item response theory. However the use of modern test theory much rely on availability of the computer software. In this paper we report the development of a web-GUI interface that can be used to analyze polytomous responses, especially using partial credit and graded response models which will also contains theories and interpretations of the results. This web-GUI interface is expected to help teachers to understand and to do the analysis of polytomous responses more easily.